Pengembangan Model Pelukan HOTS Bagi Guru Sekolah Dasar - Hana Septina Kristanti; Yari Dwikurnaningsih; Wasitohadi Wasitohadi (Graduate School of Universitas Negeri Malang, 2020)
Abstract: This study aims to describe the existing HOTS learning training, its strengths and weaknesses, and to develop a HOTS learning inductive training model for elementary school teachers. This research method is R&D. The research results reveal: (1) teacher training on HOTS so far has only focused on preparing HOTS questions, (2) training so far has not answered the needs of elementary school teachers both in terms of material and self-development. Strengths all primary schools, both public and private, have teacher representatives who have received training on HOTS topics, and (3) creation of HOTS Hugging Model for Elementary School Teachers who have advantages over existing training models. The conclusion is that the training model product falls into the very good criteria after being validated by 3 experts. The test results are in the good category.Abstrak: Penelitian ini bertujuan untuk mendeskripsikan pelatihan pembelajaran HOTS yang ada selama ini, kelemahan dan kelebihannya, serta mengembangkan model pelatihan induktif pembelajaran HOTS bagi guru SD. Metode penelitian ini adalah R&D. Hasil penelitian mengungkap (1) pelatihan guru tentang HOTS selama ini hanya berfokus pada penyusunan soal HOTS, (2) pelatihan selama ini belum menjawab kebutuhan guru SD baik dari segi materi maupun segi pengembangan diri. Kelebihan, semua SD baik negeri maupun swasta, sudah ada perwakilan guru yang mendapatkan pelatihan dengan topik HOTS, (3) terciptanya Model Pelukan HOTS bagi guru SD yang memiliki keunggulan dibandingkan dengan model pelatihan yang sudah ada. Kesimpulan produk model pelatihan masuk pada kriteria sangat baik setelah divalidasi oleh tiga pakar. Hasil ujicoba produk pada kategori baik.